Repercussions of redundancy : a local survey - Kahn, Hilda R. (London : G. Allen and Unwin, 1964)
A high proportion of dismissals in the British Motor Corporation and other firms occurred in Birmingham, and it was there that the sample was drawn on which Dr. Kahn bases her report. Two years after the dismissals, 486 men were interviewed to discover their employment records and their reactions to redundancy. Most of the questions were open ended so that the respondents were not confined to pre- selected answers. Dr. Kahn in this book presents a commentary illustrated by 86 little tables, a product of patience and imagination, in effect oddly reminiscent of the Bayeux tapestry. The relevant characteristics of the men are described; the impact of the sudden loss of job; the mechanics of job seeking; types of jobs held; adjustments in family finances; use of social services and trade unions; attitudes towards redundancy.
Stamped on t.p.: Distributed by Sportshelf, New Rochelle, N.Y.
Bibliographical footnotes.
rpm 05/04/2018
Loans
Keywords: Unemployed; Labor supply